Subject Mentoring in the Secondary School - Arthur J. James (London, Routledge, 2003)
Student teachers have always worked with professionals during their teaching practice, but as teacher training becomes more school based, the role of the mentor has become much more important. Even newer is the emergence of the subject mentor.This book is an examination of the nature of effective mentoring and its contribution to student teacher development. Part One of the book has a broad perspective and looks at policy developments and the differing approaches to teacher education. Part Two explores central issues which have emerged in the author's research with mentors. It identifies tendencies in subject mentoring which characterise the work of subject mentors in schools, and key aspects of mentoring are examined, such as collaborative teaching, observation and the practice of discursive mentoring.